2016
DOI: 10.20996/1819-6446-2016-12-3-277-284
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Right Ventricular Diastolic Function in Patients With Ischemic Heart Disease in Different Age Groups

Abstract: Диагностика дисфункции правого желудочка (ПЖ) имеет большое значение у больных кардиальной па-тологией. Так, ее наличие позволяет выявлять среди пациентов с хронической сердечной недостаточ-ностью (ХСН) лиц с крайне неблагоприятным про-гнозом -продолжительностью жизни менее 2 лет [1]. При декомпенсации ХСН наилучшими прогностиче-скими критериями были низкий индекс давления со-кращения ПЖ и высокое расчетное давление в правом предсердии (ПП) [2]. У больных с ХСН с сохраненной фракцией выброса левого желудочка (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…An investigation by Fenster et al 15 demonstrated that diastolic dysfunction was able to independently influence exercise tolerance in subjects with chronic obstructive pulmonary disease. Gajfulin et al 16 evaluated diastolic dysfunction in ischemic heart disease and found an increase in A TV and a reduction in the E/A TV ratio and e'/a' TV among their study population. Some previous investigations on patients with dilated or ischemic cardiomyopathy, pulmonary hypertension, and congenital heart disorder have validated the role of E/e' TV in predicting mortality and readmissions 17‐19 .…”
Section: Discussionmentioning
confidence: 95%
“…An investigation by Fenster et al 15 demonstrated that diastolic dysfunction was able to independently influence exercise tolerance in subjects with chronic obstructive pulmonary disease. Gajfulin et al 16 evaluated diastolic dysfunction in ischemic heart disease and found an increase in A TV and a reduction in the E/A TV ratio and e'/a' TV among their study population. Some previous investigations on patients with dilated or ischemic cardiomyopathy, pulmonary hypertension, and congenital heart disorder have validated the role of E/e' TV in predicting mortality and readmissions 17‐19 .…”
Section: Discussionmentioning
confidence: 95%